Anthropic action affects the cuticular chemical profile of social wasps - Sguarizi-Antonio, Denise; Batista, Nathan Rodrigues; Michelutti, Kamylla Balbuena; Soares, Eva Ramona Pereira; Solórzano, Julio César Jut; Cardoso, Claudia Andrea Lima; Lima-Júnior, Sidnei Eduardo; Torres, Viviana de Oliveira; Antonialli-Júnior, William Fernando (Papéis Avulsos de Zoologia, 2022)
As a result of environmental change by anthropic action, animal species that inhabit these areas may suffer the effects of it on their phenotypes as a consequence of adapting to these conditions. In the case of social wasps, cuticular chemical compounds may be influenced, since these vary depending on genetic and environmental factors. However, few studies have investigated the synanthropic effects over the cuticular surface of social wasps. Therefore, the aim of this study was to investigate how cuticular compounds vary according to the different degrees of human activity and test the hypothesis that cuticular compounds of social wasps are affected by the level of anthropic activity in which their nests are found. Data on the cuticular chemical compounds composition of colonies of 3 species of social wasps were used along with the level of anthropization of their nesting sites in four municipalities in the state of Mato Grosso do Sul, Brazil. From the geographical coordinates of the sampling sites, the percentages of urban construction areas, agriculture, water body, vegetation and exposed land were calculated, and the nesting sites of the colonies were classified as more or less anthropized areas. The chemical profile was determined by extraction of cuticular compounds and analyzed by Gas Chromatography coupled to Mass Spectrometer (GC-MS). The results show that the cuticular chemical composition of the individuals of these species is affected by the level of anthropization in their nesting sites, with a qualitative and quantitative variation that must be tied not only to genetic differences, but, above all, to the local environmental conditions to which their colonies are subjected.